Author Correction: Balance training improves memory and spatial cognition in healthy adults. Issue 1 (December 2018) - Rogge, Ann-Kathrin; Röder, Brigitte; Zech, Astrid; Nagel, Volker; Hollander, Karsten; Braumann, Klaus-Michael; Hötting, Kirsten
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.